SUPERVISI PENDIDIKAN UNTUK MENINGKATKAN KUALITAS GURU SECARA EFEKTIVITAS DAN EFISIENSI - Suci; Ramia Saputri; Sulkaidah Kanang; Nurhayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Supervision is one of the activities provided to improve the quality of a teacher, which is a component of human resources that must be nurtured and developed comprehensively and continuously to reach an effective and efficient level. In this journal, to improve the quality of developing a teacher to become a professional, educational supervision is required. Supervision in schools is carried out by the principal who is tasked as a supervisor to guide teachers in the learning process so that they do not deviate from the main goals of education, so he must be able to carry out various supervision and control to improve teacher performance to become an effective and efficient teacher. This supervision and control is a preventive measure to prevent teachers from making mistakes and to be more careful in carrying out their work as educators. This journal uses the